ANALYSIS OF THE IMPLEMENTATION OF THE FAMILY QUALITY IMPROVEMENT PROGRAM IN REALIZING GENDER EQUALITY IN BANDUNG CITY - Mutaqin, Nazharra Nurazka; Rachmawati, Bahagia Nadia; Ara’af, Raras Ajeng Anyelir; Saefulrahman, Iyep (LPPM Univ. Ibn Khaldun Bogor, 2026)
Gender equality is a development priority in various countries and is one of the main objectives of the Sustainable Development Goals (SDGs), especially SDG 5. In the Indonesian context, one of the key strategies to achieve it is through improving the quality of the family as a basic institution in the formation of social norms. This study aims to analyze the implementation of the family quality improvement program run by the Bandung City Women's Empowerment and Child Protection Agency (DP3A) and evaluate the extent to which the program reflects the principles of Gender Responsive Governance (GRG) and contributes to the achievement of SDG 5. Using a qualitative policy research approach, data were obtained through interviews with DP3A officials as well as studies of regulatory documents and statistical data. The research findings indicate that the DP3A plays a primary role as a coordinator within a cross-sectoral ecosystem encompassing other government agencies, community organizations, and pentahelix partners. Several programs, such as PUSPAGA (Fathers' School), Sekolah Ayah (Fathers' School), Sekolah Remaja (Youth School), and the Keluarga 2P (Family 2P) movement, have successfully improved parenting literacy and gender awareness. However, challenges persist, including budget constraints, minimal male representation in family programs, and low achievement of objectives such as the Gender Development Index (GDI). This article concludes that policy implementation has reflected GRG principles, but its impact on changing gender norms still requires ongoing intervention. Recommendations are provided for institutional aspects, service expansion, and strengthening data integration across agencies